Subsidies, Information, and the Timing of Children's Health Care in Mali - Anja Sautmann; Samuel Brown; Mark Dean (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study how healthcare subsidies and improved information affect over- and under-use of primary healthcare in a randomized control trial of 1544 children in Mali. In a dynamic model of healthcare demand, misuse relative to policymaker preferences (here given by WHO care-seeking standards) arises from seeking care too early or too late during an illness spell. Using nine weeks of daily data, we show that the barrier to optimal care seeking is cost, not information: subsidies increase demand by over 250%, but overuse is rare with or without the subsidy. Information, contrary to intent, appears to increase underuse, as our model predicts.
Keywords: 330; primary healthcare; subsidies; healthcare demand